Enterococcal Endocarditis: Hiding in Plain Sight - Barnes, Aaron M. T.; Frank, Kristi L.; Dunny, Gary M. (Frontiers in Cellular and Infection Microbiology, 2021)
Enterococcus faecalis is a major opportunistic bacterial pathogen of increasing clinical relevance. A substantial body of experimental evidence suggests that early biofilm formation plays a critical role in these infections, as well as in colonization and persistence in the GI tract as a commensal member of the microbiome in most terrestrial animals. Animal models of experimental endocarditis generally involve inducing mechanical valve damage by cardiac catheterization prior to infection, and it is often presumed that endocarditis vegetation formation resulting from bacterial attachment to the endocardial endothelium requires some pre-existing tissue damage. Here we review both historical and more recent animal model studies demonstrating the robust ability of E. faecalis to attach and form stable microcolony biofilms encased within a bacterially-derived extracellular matrix on both healthy endovascular endothelium and gastrointestinal epithelium. We propose that this phenotype may allow the organism to persist as an undetected infection in asymptomatic individuals and thus provide an infectious reservoir for later clinical endocarditis.